Readers in the round: children’s holistic engagements with texts - Parry, Becky; Taylor, Lucy (Wiley, 2018)
In this paper we demonstrate the relationship between reading and writing for pleasure. Children read a wide range of media as well as books for pleasure and develop strong affective bonds with the artefacts of literacy they encounter. What remains less well understood is the relationship between the array of texts children engage with and the texts they subsequently create. A focus on ‘Reading for Pleasure’ has enabled us to think anew about the relationships between the texts children read, play and engage with and those they make, play and tell. Data from two doctoral research projects illuminates the ways children draw on cultural resources, moving skilfully across mode, medium and form. In doing so they learn language conventions which enable them to engage in schooled literacies and learn to use conventional language techniques for their own purposes to transform and re-imagine texts. Children’s identities as readers, writers, and storytellers are constructed holistically and we explore the role of pleasure in reading and meaning making. In conclusion we consider the potential for positioning reading for pleasure not in isolation, but as a strand in the complex fabric of literacy that needs to be nurtured in children.